2015
DOI: 10.17756/jrds.2015-006
|View full text |Cite
|
Sign up to set email alerts
|

Using the Neuroadaptagen KB200z™ to Ameliorate Terrifying, Lucid Nightmares in RDS Patients: the Role of Enhanced, Brain-Reward, Functional Connectivity and Dopaminergic Homeostasis

Abstract: BackgroundLucid Dreams are a form of dream life, during which the dreamer may be aware that he/she is dreaming, can stop/re-start the dreams, depending on the pleasantness or unpleasant nature of the dream, and experiences the dream as if he/she were fully awake. Depending on their content, they may be pleasant, un-pleasant or terrifying, at least in the context of patients, who also exhibit characteristics of Reward Deficiency Syndrome (RDS) and Posttraumatic Stress Disorder (PTSD).Case SeriesWe present eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The latter effect may suggest an important brain mechanism called “neuroplasticity.” While the authors have, to date, published two papers showing that KB220z eliminates life-long, frequently terrifying lucid dreams, our most recent findings show a prolonged effect of KB220Z in the elimination of these nightmares, and potential conversion to happy lucid dreams up until 12 months. These clinical findings suggest the possibility of KB220Z-induced for neuroplasticity (McLaughlin, Blum, Oscar-Berman, Febo, Agan, et al, 2015; McLaughlin, Blum, Oscar-Berman, Febo, Demetrovics, et al, 2015). …”
Section: Neuroimaging Studiesmentioning
confidence: 69%
“…The latter effect may suggest an important brain mechanism called “neuroplasticity.” While the authors have, to date, published two papers showing that KB220z eliminates life-long, frequently terrifying lucid dreams, our most recent findings show a prolonged effect of KB220Z in the elimination of these nightmares, and potential conversion to happy lucid dreams up until 12 months. These clinical findings suggest the possibility of KB220Z-induced for neuroplasticity (McLaughlin, Blum, Oscar-Berman, Febo, Agan, et al, 2015; McLaughlin, Blum, Oscar-Berman, Febo, Demetrovics, et al, 2015). …”
Section: Neuroimaging Studiesmentioning
confidence: 69%
“…In terms of positive sleep aspects, earlier studies have shown that KB220Z can actually improve sleep [ 52 ] and even eliminate posttraumatic stress disorder (PTSD)/ADHD induced unwanted terrifying lucid dreams [ 53 54 ]. Along these lines, qEEG studies utilizing KB220Z has revealed reduced widespread theta activity with concomitant increase in both alpha and low beta waves in abstinent psychostimulant abusers [ 37 ] as well as in alcoholics and heroin addicts [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…She also noted increased “mental energy;” during this time, she took the KB220Z. Later, she reported that she no longer had lucid dreams, despite having stopped the KB220Z 2 years prior ( McLaughlin, Blum, Oscar-Berman, Febo, Agan, et al., 2015 ; McLaughlin, Blum, Oscar-Berman, Febo, Demetrovics, et al., 2015 ; McLaughlin et al., 2016 ).…”
Section: Case Reportmentioning
confidence: 99%